Digital marketing of unhealthy foods and non-alcoholic beverages to children and adolescents: A narrative review - Fretes, Gabriela; Veliz, Paula; Narvaez, Ana Maria; Williams, D’Arcy; Sibille, Romain; Arts, Maaike; Leroy, Jef L. (Elsevier, 2025)
With growing access to electronic devices and time spent online, the food and beverage industry increasingly uses digital media to market unhealthy foods and non-alcoholic beverages (high in unhealthy fats, sugars, and/or salt and often highly processed) to children and adolescents. We conducted a narrative review of the global evidence on digital marketing of these foods and drinks and studied policies and regulations in Latin American and Caribbean (LAC) countries. Evidence was limited to a few high, upper-middle and lower-middle income countries where children and adolescents were found to be extensively exposed to the digital marketing of unhealthy foods and non-alcoholic beverages and this exposure increased with age. A wide range of purposefully designed marketing techniques were used. Exposure to the digital marketing of unhealthy foods appears to be followed by increased consumption, but the quality of the evidence was limited. Accurate assessment of exposure was a shortcoming in most studies. Stronger evidence will require studies with more rigorous designs that minimize confounding and objectively quantify individual exposure. Mandatory comprehensive policies are needed that limit exposure of children and adolescents to the marketing of unhealthy foods and non-alcoholic beverages irrespective of the medium or platform they use. The experience of LAC countries may provide insights for the development of effective policies in other countries. Novel technologies that can be used by governments to monitor digital marketing regulations are needed.